2012
DOI: 10.2169/internalmedicine.51.6058
|View full text |Cite
|
Sign up to set email alerts
|

Hypogammaglobulinemic Patient with Polyarthritis Mimicking Rheumatoid Arthritis Finally Diagnosed as Septic Arthritis Caused by Mycoplasma hominis

Abstract: Hypogammaglobulinemia is a reduction or absence of immunoglobulin, which may be congenital or associated with immunosuppressive therapy. In addition to infectious diseases, autoimmune diseases have also been reported in patients with hypogammaglobulinemia. A 26-year-old man with hypogammaglobulinemia had multiple joint pain and swelling with erosive changes in the proximal interphalangeal joint of the right middle finger on X-ray film, mimicking rheumatoid arthritis (RA). As polyarthritis remained after immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In 2009 Kang et al showed that downregulation of HSP70 protects rheumatoid arthritis fibroblast-like synoviocytes from NO-induced apoptosis [31]. Interestingly, M. hominis is known to be associated with arthritis [32] with symptoms similar to rheumatoid arthritis [33] known to be the result of an autoantibody response.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009 Kang et al showed that downregulation of HSP70 protects rheumatoid arthritis fibroblast-like synoviocytes from NO-induced apoptosis [31]. Interestingly, M. hominis is known to be associated with arthritis [32] with symptoms similar to rheumatoid arthritis [33] known to be the result of an autoantibody response.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only 16 cases of central nervous system (CNS) infection caused by M. hominis have been described since 1950 (Table 1). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] A new case of meningitis caused by this bacterium in an adult, following a neurosurgical procedure, is reported here.…”
Section: Introductionmentioning
confidence: 99%
“…The recent cases describe isolation of M. hominis a number of days following hospital admission with patients having contributing factors such as head trauma, neurosurgery, genitourinary or delivery manipulations 1–16. A separate group at increased risk of extra-genital M. hominis infections are those with congenital and acquired immunodeficiency due to impaired cell-mediated and antibody-mediated immunity; these include immune-suppressive therapy post organ transplantation, collagen vascular disease and hypogammaglobulinaemia,16 18 19…”
Section: Discussionmentioning
confidence: 99%
“…Extra genital sites of infection include vascular site infections, surgical wounds, joint infection and respiratory tract infections,16 18 19 As described, M. hominis has also emerged as an infrequent but important cause of postoperative central nervous system infections. M. hominis asymptomatically colonises the urogenital tract (15%) and more rarely the respiratory tract mucosa of healthy individuals 1–16.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation